A methodology for the assessment of compound sea level and rainfall impact on urban drainage networks in a coastal city under climate change. (December 2021) - Laster Grip, Isabelle; Haghighatafshar, Salar; Aspegren, Henrik
Highlights: An urban drainage network was assessed under compound hydrometeorological events. A methodology was developed incorporating long-term rain and sea-level dynamics. Future climate projections were generated based on the emission scenario RCP8.5. Rainfall is found to be the main flooding stressor in today's climate condition. Storm surges become the dominating stressor for drainage failure after 2075. Abstract: This study seeks to investigate how stormwater drainage systems in coastal cities respond to climate change in terms of simultaneous sea level rise and rainfall. 7.5 years of recorded rainfall and sea level data in the city of Trelleborg in Sweden were used to generate projections of future climate events based on the emission scenario RCP8.5. Twelve scenarios were formulated to represent rain and sea level in today's (reference)- and future climate. Future rainfall was computed using regional climate model data together with the Delta Change Method. Sea-related data was represented with two variables, namely an average sea level and storm surges. The average sea level was calculated to reflect seasonal variation using a second-order Fourier analysis whilst raw gauge data was used to capture the storm surges. The two sea variables were then scaled to represent future projections of sea level rise and storm surges in the study area. The performance of the drainage system was simulated with MIKE Urban 1D model and the results were expressed through two indicators, number of flooded nodes and flood frequency . The results of this study reveal a tipping point is likely to be found between years 2075 and 2100, after which storm surges become a major driver for overwhelmed drainage system. It was also found that pluvial floods may become more likely and frequent during winters as time progresses. This has a great implication when deciding on adaptation measures.